Influence of mixed gel structuring with different degrees of matrix inhomogeneity on oral residence time. (December 2016) - Laguna, L.; Sarkar, A.
Abstract: The aim of this study was to examine the influence of structuring mixed biopolymer gels with different degrees of inhomogeneity on oral residence time. Ten model gels with varying mechanical and structural properties were prepared using κ -carrageenan and sodium alginate at concentrations ranging from 0 to 4 wt%. In few of the mixed gel systems, structural inhomogeneity was introduced by incorporation of calcium alginate beads of different sizes, later made by syringe extrusion or spraying techniques. The gels were characterized by dynamic oscillation, fracture behaviour and the structural details were evidenced in different length scales by cryo-scanning electron microscopy (cryo-SEM) and transmission electron microscopy (TEM). In parallel, gels were characterized by quantitative descriptive analysis (QDA™). Oral processing behaviour was assessed in terms of oral residence time, number of chews and difficulty perceived by eleven young participants. A decrease in the gel fracture point with the addition of calcium alginate beads was attributed to the interruption of the continuous κ -carrageenan gel network, as revealed in the Cryo-SEM and TEM images and with narrower linear viscoelastic region. When the mixed gel network included κ -carrageenan with sodium alginate, the linear viscoelastic range was extended, but the gel strength was lower than κ -carrageenan alone highlighting the incompatibility between the biopolymers. Oral residence time was highly dependent on the number of chews and to a certain extent on the difficulty perceived. Oral residence time and number of chews were positively correlated with gel strength, degree of network inhomogeneity in terms of particle size of the beads. Graphical abstract: Highlights: Mixed gel systems with κ -carrageenan and Na- or Ca-alginate were created. κ -carrageenan network was weakened by the presence of defects (Ca-alginate beads). Oral residence time was positively correlated with degree of matrix inhomogeneity. Results may help to design food for elderly with diverse oral processing properties.